Influence of Spatial Selectivity of Radiation of Mobile Communication Base Stations on the Level of Electromagnetic Background Introduced by them - V. I. Mordachev; D. A. Tsyanenka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Radio frequency electromagnetic radiation from base stations is the main source of electromagnetic background generated by mobile (cellular) communication systems in residential areas; its intensity makes a significant contribution to the level of electromagnetic pollution of the habitat and determines the level of electromagnetic safety of the population. The previously proposed technique for estimating the average intensity of this background, based on the analysis of the territorial intensity of mobile traffic, takes into account the spatial selectivity of base station radiation in a simplified form by introducing the radiation directivity parameter U, equal to the inverse of the number of base station service sectors, assuming that the width of the main lobe of the radiation pattern is equal to the width of this sector and without taking into account the radiation directivity in the vertical plane, which determines the pessimistic nature of these estimates. The paper presents a refined analysis of the values of the parameter U for a two-level models of antenna radiation patterns, which reflects the real values of the width of their main lobes in horizontal and vertical planes, the relative levels of side lobes and the ratio of radiation power of the main and side lobes. The analysis was performed both for stationary sector antennas of cellular communication systems and for adaptive phased antenna arrays of 4G/5G systems capable of providing service using narrow beams. The analysis showed that the value of the U parameter of sector antennas is 5–15 dB less than the inverse of the number of sectors of base stations, and for narrow beams of adaptive antenna arrays, this difference reaches 20 dB. If tilt angles of main lobes of antenna radiation patterns with respect to the horizon are less than 30°, then at estimation of the average electromagnetic background intensity the inverse of their antenna gain in the main lobe can be used as the U parameter value of the spatial selectivity (directivity) of base stations radiations.